Examining the influence of list composition on the mnemonic benefit of errorful generation. - DiMarco, Donnelle; Laursen, Skylar J.; Churey, Katherine R.; Fiacconi, Chris M. (Memory, 2025)
Despite literature showing that errorful generation with corrective feedback enhances retention better than mere studying, it is unclear if this benefit depends on the composition of the learning list (pure error generation/read versus mixed). Here, we investigated whether the mnemonic advantage and metamnemonic evaluation of errorful generation generalise beyond mixed-list designs. Experiment 1 used a free-recall test, while Experiments 2 and 3 used a cued-recall test, with Experiment 3 also including a judgment of learning (JOL) assessment. Only when memory was tested via free recall did the benefit of errorful generation depend on experimental design, with the effect being most robust in mixed lists. Replicating past research, we too found that despite a clear mnemonic benefit for error generation in cued-recall tests, participants predicted better memory following read-only trials, and that this effect was not contingent on list composition. At the practical level, these findings demonstrate instances in which errorful generation is beneficial for memory and learning. At the theoretical level, the results fit nicely within the item-order framework in accounting for commonly observed design effects in free recall.